Exploring the Effectiveness of Body-Worn Cameras (BWCs) During Police Operations in the Province of Albay - Macabeo, Manny (JPAIR Multidisciplinary Research, 2026)
Law enforcement is a constantly evolving profession, and police officers regularly face dangerous encounters that pose a far greater risk than those experienced by the general public. Today, body-worn cameras are being used in police operations to enhance transparency, accountability, and the documentation of evidence.  This study determined the status of Body Worn Cameras in the Province of Albay, explored the effectiveness of body-worn cameras during police operations, analyzed the challenges encountered such as technical issues, ergonomic interference, and human error by the police officers in using Body Worn Cameras during Police Operations and proposed an Institutional Framework that will enhance the effectiveness of the police officers in using Body Worn Cameras during Police Operations and standardize the operating procedures by addressing the recognized challenges through structured governance, dedicated resources, and clear policies.  The study reveals that the used of Body-Worn Camera (BWC) in Albay has successfully initiated an irreversible, legally binding cultural shift toward verifiable accountability, necessitating a proposed institutional framework to mitigate these challenges and fully realize the BWC's potential as a reliable tool for law enforcement. Thus, Body Worn Cameras serve as an objective digital witness, ensuring that police officers remain accountable for their actions and maintain the highest standards of integrity during every police operation.
Keywords: Social Science; Effectiveness; Body-Worn Cameras (BWCs); Police Operations